Local Differences in Cortical Excitability – A Systematic Mapping Study of the TMS-Evoked N100 Component - Roos, Daniela; Biermann, Lea; Jarczok, Tomasz A.; Bender, Stephan (Frontiers in Neuroscience, 2021)
Transcranial magnetic stimulation with simultaneous electroencephalography (TMS-EEG) applied to primary motor cortex (M1) provides two parameters for cortical excitability: motor evoked potentials (MEPs) and TMS-evoked potentials (TEPs). This study aimed to evaluate the effects of systematic coil shifts on both the TEP N100 component and MEPs, in addition to the relationship between both parameters. In twelve healthy adults, the center of a standardized grid was fixed above the hotspot of the target muscle of the left primary motor cortex. Twelve additional positions were arranged in a quadratic grid with positions between 5 and 10 mm from the hotspot. At each of the 13 positions TMS single pulses were applied. The topographical maximum of the resulting N100 was located ipsilateral and slightly posterior to the stimulation site. A source analysis revealed an equivalent dipole localized more deeply than standard motor cortex coordinates and could not be explained by a single seeded primary motor cortex dipole. The N100 topography might not only reflect primary motor cortex activation but also summed activation of the surrounding cortex. N100 amplitude and latency decreased significantly during stimulation anterior-medial to the hotspot, while MEP amplitudes were smaller at all stimulation sites other than the hotspot. Therefore, N100 amplitudes might be suitable for detecting differences in local cortical excitability. The N100 topography, with its maximum located posterior to the stimulation site, possibly depends on both anatomical characteristics of the stimulated cortex and differences in local excitability of surrounding cortical areas. The less excitable anterior cortex might contribute to a more posterior maximum. There was no correlation between N100 and MEP amplitudes but a single-trial analysis revealed a trend toward larger N100 amplitudes in trials with larger MEPs. Thus, functionally efficient cortical excitation might increase the probability of higher N100 amplitudes, but TEPs are also generated in the absence of MEPs.